Nordic growth sectors - How can working life policies contribute to improving the framework conditions? - Nordic Council of Ministers, Copenhagen (Copenhagen, 2013)
"The Nordic welfare states are facing new challenges in an increasingly globalised world. Fiercer competition has underlined the need for the Nordics to enhance competitiveness – and to support and nurse growth in industry and businesses.